Hopelessness among adults with congenital heart disease: Cause for despair or hope?. (1st March 2017) - Eslami, Bahareh; Kovacs, Adrienne H.; Moons, Philip; Abbasi, Kyomars; Jackson, Jamie L.
Abstract: Background: Adults with congenital heart disease (CHD) face unique life courses and challenges that may negatively influence their psychological functioning. The aims of this study were to (1) examine the level of hopelessness among adults with CHD in comparison with non-CHD participants and (2) identify correlates of elevated hopelessness among adults with CHD. Methods: We enrolled 347 patients with CHD (18–64 years, 52.2% female) and 353 matched (by sex/age) non-CHD persons in this cross-sectional study. Hopelessness was assessed by Beck Hopelessness Scale. Hierarchical multiple logistic regression analyses were performed to explore correlates of elevated hopelessness. Results: The mean total hopelessness score did not significantly differ between the CHD and non-CHD groups. Twenty-eight percent of CHD patients had elevated hopelessness scores. Within the CHD patient sample, regression analyses revealed that being male (odds ratio = 2.62), not having children (odds ratio = 3.57), being unemployed (odds ratio = 2.27), and elevated depressive symptoms (odds ratio = 1.21) were significantly associated with hopelessness. Regular physical activity (odds ratio = 0.36) emerged as a protective factor and all CHD disease parameters were unrelated to hopelessness. The final model explained 43% of the variance in hopelessness. Conclusions: Adult CHD teams are encouraged to continue to explore strategies to support patients to live as rich and full as lives as possible by pursuing relationships, employment and physical activity, as well as managing depression and hopelessness.